Berberine inhibits the chemotherapy‐induced repopulation by suppressing the arachidonic acid metabolic pathway and phosphorylation of FAK in ovarian cancer. (8th October 2017) - Zhao, Yawei; Cui, Lianzhi; Pan, Yue; Shao, Dan; Zheng, Xiao; Zhang, Fan; Zhang, Hansi; He, Kan; Chen, Li
Abstract: Objectives: Cytotoxic chemotherapy is an effective and traditional treatment of ovarian cancer. However, chemotherapy‐induced apoptosis may also trigger and ultimately accelerate the repopulation of the small number of adjacent surviving cells. This study mainly focused on the tumour cell repopulation caused by chemotherapy in ovarian cancer and the adjunctive/synergistic effect of Berberine on the prevention of tumour repopulation. Materials and methods: The transwell system was used to mimic the co‐culture of surviving ovarian cancer cells in the microenvironment of cytotoxic chemotherapy‐treated dying cells. Tumour cell proliferation was observed by crystal violet staining. AA and PGE2 levels were measured by ELISA, and changes of protein expression were analysed by Western blot. Results: Chemotherapy drug VP16 treatment triggered AA pathway, leading to the elevated PGE2 level, and ultimately enhanced the repopulation of ovarian cancer cells. Berberine can block the caspase 3‐iPLA2 ‐AA‐COX‐2‐PGE2 pathway by inhibiting the expression of iPLA2 and COX‐2. Berberine can also reverse the increased phosphorylation of FAK caused by abnormal PGE2 level and thus reverse the repopulation of ovarian cancer cells after VP16 treatment. Conclusions: Our observation suggested that Berberine could inhibit the chemotherapy‐induced repopulation of ovarian cancer cells by suppressing the AA pathway and phosphorylation of FAK. And these findings implicated a novel combined use of Berberine and chemotherapeutics, which might prevent ovarian cancer recurrence by abrogating early tumour repopulation.